Identifikasi Jenis Fouling Organisme Wilayah Bahari Lestari di Desa Mayangan, Kecamatan Gumukmas, Kabupaten Jember - Rifki, Ahmad; Prasasti, Arindana Dwi; D, Adelia Septhiana; Syahputra, Ardian; Sakinah, Wazirotus; Saifurridzal, Saifurridzal; Pahlewi, Anita Diah (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2024)
this research to identify fouling organism types that can impact the sustainability of the Lestari marine region. In efforts to preserve the environment and support water resource management, the study aims to develop a comprehensive understanding of the dominant fouling organisms in this area and their potential impacts. Through this identification, it is hoped that suitable prevention and mitigation strategies can be developed to maintain the balance of the coastal ecosystem. The method used is sampling in the form of pictures and direct descriptive exploration, while identification of attached biota and mangrove types is carried out using descriptive information. The research results showed that the dominant biota came from bivalves with the type Saccostrea cucullata from the genus Ostreidae. Mangrove species are growing naturally or through replanting efforts in Mayangan Village, Gumukmas District, Jember Regency